1998
DOI: 10.1063/1.368308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic composite elastic medium theory. Part II. Three-dimensional media

Abstract: Non-self-consistent and self-consistent methods of estimating velocity and attenuation of P waves and S waves at all frequencies for heterogeneous media with three-dimensional inclusions are formulated using the scattering functions of the individual inclusions. The methods are the generalization of methods for one-dimensional media presented in the first paper of this series. The specific case of spherical inclusions is calculated with the exact scattering function and compared with several low frequency appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Gassmann, 1951;Biot, 1962;Dvorkin and Nur, 1993) and ones based on scattering theory (e.g. Kuster and Toksöz, 1974;Berryman, 1980;Kaelin and Johnson, 1998). For a porous sand or non fractured rock these relationships are relatively simple at low frequencies (less than 10 kHz): the velocity as a function of porosity and saturation is real valued and non dispersive.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gassmann, 1951;Biot, 1962;Dvorkin and Nur, 1993) and ones based on scattering theory (e.g. Kuster and Toksöz, 1974;Berryman, 1980;Kaelin and Johnson, 1998). For a porous sand or non fractured rock these relationships are relatively simple at low frequencies (less than 10 kHz): the velocity as a function of porosity and saturation is real valued and non dispersive.…”
Section: Introductionmentioning
confidence: 98%
“…Elastic wave propagation through a porous medium can be modelled using a multiple scattering approach. The approach is described in detail by Kaelin and Johnson (1998) and it therefore suffices to repeat only the basic ideas here. In a heterogeneous medium The relationship between acoustic, viscoacoustic and poroelastic wave propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic composite elastic medium theory includes multiple forward scattering from spherical pores and grains as well as intrinsic attenuation of viscous fluids (Kaelin and Johnson, 1998). The elastic P-waves and S-waves experience multiple scattering from grains and pores.…”
Section: Dynamic Composite Elastic Medium Theorymentioning
confidence: 99%
“…However, some studies on multiple scattering for the media with solid or liquid inclusions in a solid matrix found that the frequency dependence of speed and attenuation for compressional and shear waves has almost the same trends. [13][14][15] Then, assuming that the same forms as Eq. (22) …”
mentioning
confidence: 99%